A Comparative Analysis of Aerial Photo Data Processing Using Agisoft Metashape Professional and WEBODM - Pepayhosana, Ashelca Cristine; Fadly, Romi; Anisa, Rahma; Dewi, Citra (Universitas Lampung, 2025)
This study compares the results of aerial photo data processing using Agisoft Metashape and WebODM software, focusing on geometric accuracy, orthomosaic quality, and processing time. The data consisted of 504 aerial photographs captured by a WingtraOne Gen II UAV and seven Independent Check Points (ICPs). Agisoft Metashape utilized photo alignment, dense cloud generation, DEM, and orthomosaic construction, while WebODM applied auto boundary, DEM, fast orthophoto, high PC quality, and skipped 3D model generation. The geometric accuracy was evaluated using CE90 and LE90 values, and the orthophoto quality was assessed through planimetric analysis. The results showed that WebODM completed the process in 19 hours and 57 minutes, whereas Agisoft required over 3 days. Agisoft yielded better accuracy (CE90 = 0.21 m, LE90 = 0.64 m) compared to WebODM (CE90 = 0.29 m, LE90 = 0.70 m). In terms of orthophoto quality, Agisoft preserved building and bridge shapes better than WebODM.